Author Correction: Cryovolcanic rates on Ceres revealed by topography. (December 2018) - Sori, Michael; Sizemore, Hanna; Byrne, Shane; Bramson, Ali; Bland, Michael; Stein, Nathaniel; Russell, Christopher
In the version of this Letter originally published, the unit in the righty axis label in Fig. 3 mistakenly read '(m yr–1 )'; it has now been corrected to read '(m Myr–1 )'.